Diskusi Metaverse di Twitter (#Metaverse): Analisis Jejaring Sosial - R Amalina Dewi Kumalasari; Mahir Pradana; Asep Miftahuddin (Ideas Publishing, 2022)
The metaverse is increasingly developing into one of the innovations of the virtual world as a means to interact. Previous research has discussed the use of the Metaverse in various fields such as education, business, and religion, however, there is little research to understand the metaverse of what topics, brands, and terms appear in the conversation in the public sphere. This study seeks to identify which actors have an influence in conversations about the metaverse and what topics are developing in society, and opinions about the metaverse using the Twitter social media platform. Communication network analysis methods and text analysis methods are used to describe patterns in the form of structures in the network by crawling data on Twitter using Netlytic.org and Gephi software from April 14, 2022, to April 21, 2022, with the hashtag #metaverse, obtained 9,139 data sets. The results of this study indicate that the information in the #metaverse network is not dominated by one actor and the people involved in these conversations have a different diversity, the topics of conversation uploaded in the #metaverse hashtag network tend to be more about gaming and trading in digital assets such as cryptocurrencies, tokens, and NFT, only a small percentage of conversations relate the metaverse to certain topics such as education, business, government, and religion with various responses.. Metaverse semakin berkembang menjadi salah satu inovasi dunia virtual sebagai sarana untuk berinteraksi. Penelitian sebelumnya telah membahas pemanfaatan metaverse dalam berbagai bidang seperti pendidikan, bisnis, keagamaan, namun, hanya sedikit penelitian untuk memahami metaverse dari topik, merek, dan istilah apa yang muncul dalam pembicaraan di ruang publik. Penelitian ini berusaha untuk mengidentifikasi aktor-aktor mana saja yang memberikan pengaruh dalam percakapan tentang metaverse dan apa saja topik yang berkembang di masyarakat serta opini mengenai metaverse dengan menggunakan platform media sosial Twitter. Metode analisis jaringan komunikasi dan metode analisis teks digunakan untuk menggambarkan pola-pola dalam bentuk struktur dalam jaringan dengan cara crawling data pada Twitter menggunakan Netlytic.org dan software Gephi mulai dari 14 April 2022 sampai 21 April 2022 dengan tagar #metaverse didapatkan 9.139 data set. Hasil penelitian ini menunjukkan bahwa informasi di jaringan #metaverse tidak didominasi oleh satu aktor dan orang-orang yang terlibat dalam percakapan ini memiliki keragaman yang berbeda, topik pembicaraan yang diunggah dalam jaringan tagar #metaverse cenderung lebih banyak membahas game dan perdagangan aset digital seperti kripto, token dan NFT, hanya sebagian kecil percakapan yang mengaitkan metaverse dengan topik tertentu seperti pendidikan, bisnis, pemerintah dan agama dengan respon beragam.